Mycoplasma genitalium Antibiotic Resistance–Mediating Mutations in Canadian Women With or Without Chlamydia Trachomatis Infection. Issue 7 (July 2017) - Chernesky, Max A.; Jang, Dan; Martin, Irene; Hoang, Linda M.N.; Naidu, Prenilla; Levett, Paul N.; Wylie, John; Rebbapragada, Anu; Ratnam, Sam; Smieja, Marek; Weinbaum, Barbara; Getman, Damon
Abstract : Abstract: Testing remnant Aptima specimens from women infected with Chlamydia trachomatis detected 13.4% (53/396) with Mycoplasma genitalium compared with 5.4% (22/406) in matched C. trachomatis –negative women. Overall, 9.4% (provincial ranges of 3–20%) were infected with M. genitalium and resistance mediating mutations were found in 47.3% (26/55) to macrolides and 1.9% (1/53) to fluoroquinolones by sequencing. Abstract : Testing remnant Aptima specimens, Mycoplasma genitalium was more often detected in Canadian women infected with Chlamydia trachomatis compared to women without Chlamydia trachomatis . Macrolide resistance mediating mutations were found in 47.3% of Mycoplasma genitalium infections.